Socialization of Food Sovereignty Through a Communication Approach Based on Local Wisdom - Rahayu, Hilda; Mbunai, La Ode; Putri, Zahra Malinda; Sinaga, Muhammad Panca Prama Mustaqim (Jurnal Pengabdian Masyarakat, 2025)
Purpose: The objectives of this community service activity are: (1) socialization of the concept of food sovereignty to the community in building sustainable welfare. (2) increasing public understanding of the relationship between food independence and quality of life. (3) encouraging community participation in the practice of food sovereignty based on intercultural communication through deliberation. Method: The author uses a qualitative research method with a case study approach. The participants who attended included 30 individuals, and the study employed participatory observation, interviews, and documentation. Practical Applications: The results of the interviews were then analyzed thematically by the author and then grouped based on similarities in views expressed by 5 informants. Conclusion: A communication strategy rooted in local knowledge can enhance awareness; however, sustained efforts and institutional backing are essential for achieving genuine transformation through collaboration with government entities, non-governmental organizations, and the community, particularly the youth.